Synthetic versus Biological Patches for CDH: A Comparison of Recurrence Rates and Adverse Events, Systematic Review, and Meta-Analysis - Kamal, Tasnim Rowshan; Tyraskis, Athanasios; Ghattaura, Harmit; Fitchie, Angus; Lakhoo, Kokila (European Journal of Pediatric Surgery, 2022)
Objective Our systematic review aims to compare recurrence rates and complications of biological versus synthetic patches for the repair of congenital diaphragmatic herniae.Methods Studies from January 1, 1980 to April 25, 2020, with patients under the age of 16 years and with a minimum 6-month follow-up, were included from MEDLINE, Embase, and Cochrane databases. Funnel plots for recurrence rates were constructed for biological and synthetic patches. Subgroup analysis was performed for recurrence rate at the 1-year time-point and data were gathered on individual adverse events from relevant studies.Results A total of 47 studies with 986 patients (226 biological, 760 synthetic) were included. Funnel plot analysis determined overall recurrence rates of 16.7% for synthetic and 30.3% for biological patches. Subgroup analysis of 493 and 146 patients with synthetic and biological patches, respectively, showed recurrence rates of 9.9 and 26%, respectively.The most commonly used patch types—PTFE (polytetrafluoroethylene) and SIS (small intestinal submucosa)—had 11.5 and 33.3% recurrence, respectively. Adhesive bowel obstruction rates ranged from 4 to 29% in studies that systematically reported it for synthetic, and 7 to 35% for biological patches. Gastroesophageal reflux rates ranged from 25 to 48% in studies that systematically reported it for synthetic, and 21 to 42% for biological patches. Pectus deformity rates were reported as high as 80% for synthetic patches.Conclusion Biological patches appear to have higher recurrence rates than synthetic patches, while skeletal deformities are associated more commonly with synthetic patches. Results of biological patches are mainly using SIS and this may overestimate complications of current superior biological patches.
Keywords: congenital diaphragmatic hernia; diaphragmatic; patch repair; diaphragmatic hernia